What's the good of a science platform? - Gallacher, J (Royal Society, 2016)
Science may be understood as a process of knowledge generation. A science platform is an infrastructure designed to generate knowledge cost-effectively. Platforms confer advantage through increased scientific opportunity, the standardization of best practice and economies of scale. Although platforms typically involve high ‘front-loaded’ financial investment, marginal costs ‘per datum’ reduce as the volume of data increases, and the benefit–cost ratio ‘per research question’ increases as the data are exploited. In these ways, platforms enable science at scale. The efficiency of a system can only be judged in the context of a common purpose. Here, that purpose is to facilitate science (the generation of knowledge) through knowledge diversification, knowledge sharing and deepening interdependence. This goal would be well served by conditions that encourage the emergence of a highly collaborative, mutually stimulating and selforganizing scientific community.